Tradisi Ritus Tikam Dabus Dan Solidaritas Sosial Antara Desa Kilbat Dan Kilimoy Di Kecamatan Tutuk Tolu Kabupaten Seram Bagian Timur - Yani Talakua (Jayapangus Press, 2019)
This research aim to ( 1) to know the meaning of tradition ritus stab the dabus ( 2) to know the mechanism of tradition ritus stab the dabus ( 3) to know the target of tradition ritus stab the dabus ( 4) to know the process in tradition ritus stab the dabus ( 5) to know the participation of society of Countryside of Kilbat and Kilmoy to tradition ritus stab the dabus ( 6) to know the understanding of society of about solidarity. Research type used in this research is descriptive qualitative with aim to for the mendeskripsikan of or explain the event that happened at a period of/to now which is pursuant to at fact in field. Data collecting use the direct observation and interview. To look for the data validity use and trianggulasi method. Technique analyse the data use the model analyse namely phase reduce the data, phase of presentation of data and phase conclude. Pursuant to research result, inferential ( 1) Reason of society remain to preserve the tradition ritus stab the dabus of because tradition ritus stab the dabus represent the heritage from ancestors so that is obliged to preserve. ( 2) Reason of society of Countryside of Kilbat and Kilmoy execute the tradition ritus stab the dabus because to take care of and tighten the concept of life tafilidan or life of people basudara. Form the participation of society of Countryside of Kilbat and also Countryside Kilmoy in carrying out tradition ritus stab the dabus . First is in the form of physical or energy. Form the second participation is involvement mentally and emotional, Third in the form of Items.